On the respiratory rate of some macrophytic algal species near the Romanian Black Sea shore - Bologa, Alexandru S. (Cercetări Marine - Recherches Marines, 2026)
The present paper is dealing with the determination of the respiratory rate of 10 macrophytes algal species from the Romanian sea shore and the establishment of the correlation between morphological conformation and the value of respiratory rate. The values of the respiratory rate confirm interspecifically differences depending on systematic affiliation as well as on interdependence between morphology of thallus and intensity of O2 uptake. The knowledge of the value of respiratory rate offers some explanation about the understanding of the level of development of metabolic activity in algal organisms in determinate ecological conditions.